2022
DOI: 10.3389/fnut.2022.861880
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of a Low-Glycemic Diet on Serum Metabolites and Gut Microbiota in Obese Women With Prevotella and Bacteriodes Enterotypes: A Randomized Clinical Trial

Abstract: Generalized healthy eating patterns may not benefit everyone due to different genetics and enterotypes. We aimed to compare the effects of a low-glycemic diet representing the Korean traditional balanced diet (Low-GID) and westernized diet as a control diet (CD) on anthropometry, serum metabolites, and fecal bacteria in a randomized clinical trial according to enterotypes. We recruited 52 obese women aged 30–50 years, and they consumed Low-GID and CD meals for 1 month, with a 1-month washout period, in a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Whole grain intake is prospectively and inversely associated with abdominal obesity in adults in the Framingham Offspring cohort and HUNT study ( 38 , 39 ). However, a white rice-main diet with a lower nutrient score similar to RMD is positively associated with obesity and MetS risk ( 8 , 40 ). In Korea, a WSD high in noodles, bread, and meats, is positively associated with MetS risk, and KBD alleviated dyslipidemia in RCT ( 9 , 10 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole grain intake is prospectively and inversely associated with abdominal obesity in adults in the Framingham Offspring cohort and HUNT study ( 38 , 39 ). However, a white rice-main diet with a lower nutrient score similar to RMD is positively associated with obesity and MetS risk ( 8 , 40 ). In Korea, a WSD high in noodles, bread, and meats, is positively associated with MetS risk, and KBD alleviated dyslipidemia in RCT ( 9 , 10 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns have been studied over the last decade to explore ways to reduce MetS risk while ensuring adherence. Korean-balanced diets have been shown to have an inverse association with MetS risk in randomized clinical trials (RCT) and observational studies ( 8 10 ). RCT studies are limited in the aspects of intervention periods and diet types to show the effects of traditional Korean diets.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial community in the enterotypes with overlap can be switched under specific circumstances, such as changing diets. In a randomized controlled trial (RCT) with Korean-style and westernized-style diets, the participants were observed to be ET-B and ET-P. Only 10–15% of them switched enterotype, mainly those with overlapping bacteria compositions despite different enterotypes [ 32 ]. Therefore, the enterotype itself does not act as a biomarker for a specific disease, but the bacteria affecting the diseases need to be isolated in each enterotype.…”
Section: Discussionmentioning
confidence: 99%
“…We applied generalised multifactor dimensionality reduction to pinpoint the genetic variants that interact and were linked with the risk of stroke. We chose the best genetic model based on specific criteria: a significant P value ( P < 0·05) from the sign test of trained balance accuracy and test balance accuracy, along with a strong cross-validation consistency score of 9 or 10 out of 10 (20) . We computed a PRS to quantify genetic risk by summing the risk alleles across the genetic variants within the selected optimal model.…”
Section: Methodsmentioning
confidence: 99%